La portée de la formule to einai isa theō en Ph 2.6 - Focant, Camille (New Testament studies, 2016)
What is the meaning of the expression to einai isa theō when set within its original context? In this article it is argued that in Philippians 2.6b Paul asserts that Christ did not consider it an advantage to be regarded as equal to a god (or to God). This argument is developed by way of an examination of the structure of the hymn of Philippians 2.6-11, a philological analysis of v. 6, and a contextualisation of the Christ-hymn addressed to Christians living in Philippi, a Roman colony which was like a Rome in miniature.